Legal Review of the Criminal Act of Body Shaming on Social Media According to The New KUHP and Information and Transaction Electronic (ITE) Regulations - Widia Putri; Lola Yustrisia (Fakultas Hukum Universitas Djuanda, 2025)
The rapid development of technology today has caused new crimes to emerge, for example the crime of insulting body shaming committed through social media such as Facebook, Twitter, Instagram, WhatsApp and so on, where body shaming has a very bad impact on victims. The formulation of the problem is to find out how the regulation of body shaming insults through social media according to the New Criminal Code and the ITE Law and to find out how law enforcement against victims of body shaming insults on social media. Using normative juridical research methods. The results of the research explain that the regulation of body shaming insults is regulated in Article 436 referring to Law Number 1 of 2023, the Criminal Code only reaches offline insult offenses and Article 27A of Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning ITE only reaches insults in the cyber world. The government should make a law by containing one article that specifically regulates the criminal offense of insulting body shaming so that the handling can be more efficient and does not cause multiple interpretations.